Quality of routine hospital birth records and the feasibility of their use for creating birth cohorts - Murray, J; Saxena, S; Modi, N; Majeed, A; Aylin, P; Bottle, A; Medicines for Neonates Investigator Group (Oxford University Press, 2012)
Background Linkage between routinely collected hospital birth and other records offers the potential for epidemiological and public health research by developing population-level birth cohorts with cradle-to-grave follow-up. Data from births in English National Health Service hospitals are collected in the Hospital Episode Statistics (HES) database but are of uncertain quality. Methods We examined the range and completeness of birth information recorded in HES and tested an approach for minimizing the effect of hospital-level variations by selecting hospitals with high completeness of recording (≥90%) for key fields. We discuss important methodological considerations when using routine healthcare data to develop a birth cohort. Results The proportion of missing data in key birth record fields has been decreasing annually, such as gestational age and birth weight (from 46.2 and 43.9% in 2005/06 to 18.1 and 16.9% in 2009/10, respectively). We compared the important characteristics such as size and access to specialist neonatal care between 71 high-coding and 85 low-coding hospitals and found no significant differences, suggesting hospitals with high birth record completeness may be generalizable and representative of all hospitals. Conclusions The completeness of recording of hospital birth information varies greatly between hospitals in England but is improving. It may be preferable and valid to construct cohorts from only hospitals with high completeness of recording.